Combating Soil Drought in Maize (Zea mays L.): Genetic-Engineering Strategies for Drought Tolerant Varieties - Moch. Rosyadi Adnan; Ahmad Robiul Syawaluddin; Alvianti Maulidatus Sholehah; Dinik Dwi Cahyani; Fitriyatul Lailiyah; Gilang Hardi Sucahyo; Hendri Kurniawan; Nurul Aini; Elly Daru Wilujeng (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2024)
Drought is the global challenge of crop agriculture across the globe. The detrimental effect of drought hinders a significant growth and development impairment leading to devastating harvest losses. Maize, a vital staple for food faces future challenges with a rapidly expanding drought area. To address this challenge, scientists and breeders are urged to develop new varieties that are not only resistant or tolerant but also even potentially thrive under drought planting conditions. New breeding technologies involving molecular biology and biotechnology have been developed and implemented thus offering a promising solution. Genetic engineering has allowed humans to straightforwardly transfer beneficial genes across species and varieties, thus deliberating gene pool transfer of similar species and varieties. Furthermore, this technology has evolved to the level of creation, deletion, or modification of existing alleles with high precision through CRISPR/Cas9-mediated genome editing. This review article delves into the morpho-physiology, biochemical, and molecular responses of maize varieties against drought stress. It subsequently explores how genetic engineering has been utilized to optimize the selected genes underlying those responses. By exploring the current progress of genetic engineering, this article aims to prepare the ground for future advancement in combating drought through drought-tolerant maize varieties. Thus, this review article has the potential to contribute to improving food security in the increasing drought challenges.